Performative Realism - Tortzen Bager, Lene (Peripeti, 2024)
Anmeldelse af Performative Realism – Interdisciplinary Studies in Art and Media Eds. Rune Gade og Anne Jerslev Museum Tusculanum Press, 2005 University of Copenhagen